Expansion of Clinical and Genetic Spectrum of DDX3X Neurodevelopmental Disorder in 23 Chinese Patients - Dai, Yuwei; Yang, Zhuanyi; Guo, Jialing; Li, Haoyu; Gong, Jiaoe; Xie, Yuanyuan; Xiao, Bo; Wang, Hua; Long, Lili (Frontiers in Molecular Neuroscience, 2022)
Aim De novo DDX3X variants account for 1–3% of unexplained intellectual disability cases in females and very rarely in males. Yet, the clinical and genetic features of DDX3X neurodevelopmental disorder in the Chinese cohort have not been characterized. Method A total of 23 Chinese patients (i.e., 22 female and 1 male) with 22 de novo DDX3X deleterious variants were detected among 2,317 probands with unexplained intellectual disability (ID) undertaking whole exome sequencing (WES). The age, sex, genetic data, feeding situation, growth, developmental conditions, and auxiliary examinations of the cohort were collected. The Chinese version of the Gesell Development Diagnosis Scale (GDDS-C) was used to evaluate neurodevelopment of DDX3X patients. The Social Communication Questionnaire (SCQ)-Lifetime version was applied as a primary screener to assess risk for autism spectrum disorder (ASD). Result A total of 17 DDX3X variants were novel and 22 were de novo. Missense variants overall were only slightly more common than loss-of-function variants and were mainly located in two functional subdomains. The average age of this cohort was 2.67 (±1.42) years old. The overlapping phenotypic spectrum between this cohort and previously described reports includes intellectual disability (23/23, 100%) with varying degrees of severity, muscle tone abnormalities (17/23, 73.9%), feeding difficulties (13/23, 56.5%), ophthalmologic problems (11/23, 47.8%), and seizures (6/23, 26.1%). A total of 15 individuals had notable brain anatomical disruption (15/23, 65.2%), including lateral ventricle enlargement, corpus callosum abnormalities, and delayed myelination. Furthermore, 9 patients showed abnormal electroencephalogram results (9/23, 39.1%). Hypothyroidism was first noted as a novel clinical feature (6/23, 26.1%). The five primary neurodevelopmental domains of GDDS-C in 21 patients were impaired severely, and 13 individuals were above the “at-risk” threshold for ASD. Interpretation Although a certain degree of phenotypic overlap with previously reported cohorts, our study described the phenotypic and variation spectrum of 23 additional individuals carrying DDX3X variants in the Chinese population, adding hypothyroidism as a novel finding. We confirmed the importance of DDX3X as a pathogenic gene in unexplained intellectual disability, supporting the necessity of the application of WES in patients with unexplained intellectual disability.